'Too-much-of-a-good-thing'? The role of advanced eco-learning and contingency factors on the relationship between corporate environmental and financial performance. (15th August 2018) - Latan, Hengky; Chiappetta Jabbour, Charbel Jose; Lopes de Sousa Jabbour, Ana Beatriz; Renwick, Douglas William Scott; Wamba, Samuel Fosso; Shahbaz, Muhammad
Abstract: Inspired by the natural-resource-based view (NRBV) theory, we attempt to shed light on a controversy which has been persistent over the last decade, concerning the relationship between corporate environmental performance (CEP) and corporate financial performance (CFP). Using the 'too-much-of-a-good-thing' (TMGT) concept, which suggests that "too much can be worse than too little, " we link mixed results and consider the roles of advanced eco-learning and contingency factors in influencing the CEP-CFP relationship. Based on a sample composed of ISO 14001 certified companies in Indonesia, and analyzing the data using consistent Partial Least Squares (PLSc), we found that: the CEP-CFP relationship follows an inverted U-shape; advanced eco-learning is a significant predictor of the CEP-CFP relationship, meaning that organizations able to develop higher eco-learning capability will be better able to identify the ideal boundaries of investment in environmental performance without reducing their financial performance; and that contingency factors such as environmental strategy and firm size have a significant role in influencing the CEP-CFP relationship. The study's limitations, implications for practitioners and a future research agenda are also detailed. Highlights: Results show that the relationship between CEP-CFP follows an inverted U-shape. Advanced eco-learning is the key factor in improving CEP, which in turn has implications for CFP. Companies which develop eco-learning capabilities will be better investment in environmental performance.